2020
DOI: 10.1002/ana.25959
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized, Controlled, Double‐Blind Trial of Bumetanide to Treat Neonatal Seizures

Abstract: Objective In the absence of controlled trials, treatment of neonatal seizures has changed minimally despite poor drug efficacy. We tested bumetanide added to phenobarbital to treat neonatal seizures in the first trial to include a standard‐therapy control group. Methods A randomized, double‐blind, dose‐escalation design was employed. Neonates with postmenstrual age 33 to 44 weeks at risk of or with seizures were eligible. Subjects with electroencephalography (EEG)‐confirmed seizures after ≥20 and <40mg/kg phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 45 publications
2
80
2
Order By: Relevance
“…However, in a first proof‐of‐concept clinical trial on intravenous bumetanide as an add‐on to phenobarbital for treatment of neonatal seizures, bumetanide did not improve seizure control but increased the risk of hearing loss 9 . A more recent clinical trial reported a modest increase of phenobarbital's effect on neonatal seizure burden by bumetanide, 10 but, again, bumetanide was associated with increased risk of ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a first proof‐of‐concept clinical trial on intravenous bumetanide as an add‐on to phenobarbital for treatment of neonatal seizures, bumetanide did not improve seizure control but increased the risk of hearing loss 9 . A more recent clinical trial reported a modest increase of phenobarbital's effect on neonatal seizure burden by bumetanide, 10 but, again, bumetanide was associated with increased risk of ototoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…By its action on NKCC1, it blocks chloride influx and thus modulates the excitatory action of γ-aminobutyric acid (GABA) in the immature brain. 68,69 Radiprodil, a selective inhibitor of the NR2B subunit of the N-methyl-D-aspartate receptor, is also under…”
Section: T a B L E 2 Summary Of Clinical Studies And Evidencementioning
confidence: 99%
“…6 The first multicenter, randomized, double-blind clinical trial of BUM for the treatment of neonatal seizures was published recently. 7 The results of this pilot study have been long awaited for several reasons.…”
Section: Commentarymentioning
confidence: 99%